PARALLEL CINEMA AND AMBEDKAR: SIMILARITIES AND DIFFERENCES - Rai, Ashutosh Kumar; Singh, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Near parallel cinema there was resentment towards such a system embedded in society for centuries. In slave India, Ambedkar and Gandhi took it up with great volume and commitment and talked about reforming it. Through this research paper, an attempt will be made to analyse the same theories and discourses that parallel cinema gave preference to. Also, what kind of similarities and dissimilarities do they have with the points raised by Ambedkar. Three important directors of parallel cinema, Shyam Benegal 's Nishant (1975), Govind Nihalani' s Aakrosh (1980), Satyajit Ray 's Sadgati have been included for analysis. The background of the film is being studied along with the craft and narrative of these films.